Influential Article Review - The Development of Strategic Relations From The Triple To Quad Helix Innovation Models For Sustainability - Jackson, Hugh; Payne, Omar (Journal of Strategic Innovation and Sustainability, 2019)
This paper examines innovation and sustainability. We present insights from a highly influential paper. Here are the highlights from this paper: The innovative and sustainable economic development of a country depends not only on the presence of a strong government, universities, and industries but more so on how they mutually interact for strategic objectives. The evolution of these interactions has given rise to science parks, Technopolis, and at more advanced stages to innopolis. Further, common economic- and market-driven innovative demands and goals of the trio have caused the emergence of clustering and concentration of experts in various fields. However, the development and growth of the service sector, Internet and globalization have created the need for informed watchdogs for the sustainable interactions in the triple helix. Studies have revealed that the evolution of the interactions of the innovation models has increasingly raised the necessity of a strong civil society in the triple helix. This development has now transformed the triple helix into the quad helix as it is discussed in this paper. There is an urgent need for developing and middle-income countries to learn and implement the discussed global best practices of science park creation in the triple helix settings. This shall revitalize their technological innovation and gradually advance by building the infrastructure needed for competitive economic growth. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.